Triple Point of a Lennard-Jones Fluid in Nanopores with Zero Excess Pore Wall Energy - Hideki Kanda; Minoru Miyahara (Adsorption Science & Technology, 2009)
We have examined the triple points of Lennard-Jones methane confined in slit-shaped nanopores, i.e. nanopores with zero excess potential energy, using a molecular dynamics technique developed by us in a previous study. The critical condensates in the pores were cooled in a stepwise manner and the triple points determined for different pore sizes. We observed that the triple point temperature was inversely related to the pore size, identical to the Gibbs–Thomson equation. Whilst the Gibbs–Thomson equation requires adjustable parameters, our triple point model could predict the pressure and temperature without the need for such parameters. As a consequence, our model demonstrates a higher degree of generalization than the Gibbs–Thomson equation.